Sectoral Variations on Technical Efficiency and Return to Scale in the Indonesian Economy - Muchdie Muchdie (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
This paper discusses on sectoral variations of technical effciency and return to scale in the Indonesian economy. Employing regression analysis of Cobb-Douglas production function, thesecoefficientswere calculated. Nine economic sectors in the Indonesian economy: Agriculture, Mining and Quarying, Manufacturing, Electricity,Gas and Drinking Water, Construction, Trade, Hotel and Restaurant, Transportation and Communication, Finance, Rental and Corporate Services, and Services, were exercised to study the variation of those coefficiens. Sectoral data on gross domestic product, capital stock and employment are those from the years 1967 to 2007 collected from many documents available at the National Statistics Agency. The result shows that the coeffiecients of technical efficiency do vary among sectors. Those sectors in which the coefficients were above that at the national level, experienced decreasing return to scale. On the contrary, those sectors in which the coeffiecients were below that at national level, experienced increasing return to scale. DOI: 10.15408/sjie.v5i2.3400